El sentido de vida en las personas detenidas del centro de privación de libertad de la ciudad de riobamba período junio - diciembre de 2013. - Pino Acevedo, Juan Carlos (2014)
In this research it was analyzed the influence of the length of sentence of detention in sense of life of persons detained in the center of Deprivation of Liberty of Riobamba city. The confinement in centers of deprivation of liberty (also known as prison) it has been used as a method to punish or to make difficult the activity of persons who committed acts against the established norms, in the country exist a significant number of persons who are in the above mentioned centers which generate an investigation interest.